Cost-Effectiveness of Pneumococcal Vaccination in Adults in Italy: Comparing New Alternatives and Exploring the Role of GMT Ratios in Informing Vaccine Effectiveness - Vincenzo Restivo; Vincenzo Baldo; Laura Sticchi; Francesca Senese; Gian Marco Prandi; Linde Pronk; Kwame Owusu-Edusei; Kelly D. Johnson; Tim Ignacio (Vaccines, 2023)
In Italy, a sequential pneumococcal vaccination with conjugate vaccine (PCV) and polysaccharide vaccine (PPSV23) is recommended for individuals aged ≥ 65 years and those at risk for pneumococcal disease (PD) aged ≥ 6 years. The aim of this study was to assess the cost-effectiveness of the new vaccines, i.e., approved 15-valent and 20-valent PCVs. A published Markov model was adapted to evaluate the lifetime cost-effectiveness of vaccination with PCV15 + PPSV23 versus PCV13 + PPSV23, PCV20 alone, PCV20 + PPSV23, and No Vaccination. Simulated cohorts representing the Italian population, including individuals aged ≥ 65 years, those at risk aged 50–100 years, and those deemed high risk aged 18–100 years were assessed. Outcomes were accrued in terms of incremental PD cases, costs, quality-adjusted life years, life years, and the cost–utility ratio relative to PCV13 + PPSV23. The conservative base case analysis, including vaccine efficacy based on PCV13 data, showed that sequential vaccination with PCV15 or PCV20 in combination with PPSV23 is preferred over sequential vaccination with PCV13 + PPSV23. Especially in the high-risk group, PCV15 + PPSV23 sequential vaccination was dominant over No Vaccination and resulted in an ICUR of €3605 per QALY gained. Including PCV20 + PPSV23 into the comparison resulted in the domination of the PCV15 + PPSV23 and No Vaccination strategies. Additionally, explorative analysis, including the geometric mean titer (GMT) informed vaccine effectiveness (VE) was performed. In the low-risk and high-risk groups, the results of the GMT scenarios showed PCV15 + PPSV23 to be dominant over the other sequential vaccines. These findings suggest that if real-world studies would confirm a difference in vaccine effectiveness of PCV15 and PCV20 versus PCV13 based on GMT ratios, PCV15 + PPSV23 could prove a highly immunogenic and effective vaccination regime for the Italian adult population.